The “Daily Digital”: (Re)imagining Technology in Home-Based Women’s Gig Work in Egypt. - Laila Mourad (Global Labour Journal)
The gig economy is (re)shaping work and revolutionising the use of technology in everyday life. In Egypt, where more than 50 per cent of women’s enterprises are home-based, digital tools such as smartphones and social media are integral to managing informal labour practices. This paper challenges neoliberal development narratives by introducing the Daily Digital framework, a decolonial feminist lens that centres the relational and experiential dimensions of technology use. Unlike existing frameworks, it repositions the household as a site of innovation and economic agency, emphasising women’s creative strategies for (re)imagining technology and integrating it into their daily lives and work. Based on fieldwork conducted in Egypt in 2022 and 2023 with 25 home-based online food vendors, I demonstrate how women gig workers use their socially reproductive knowledges and relationalities to transform technology into a versatile tool for navigating and overcoming structural, material and social barriers, while (re)claiming and redefining their agency and mobility. This research contributes to feminist and decolonial scholarship by centring the lived experiences of women in informal economies and providing a new lens to theorise the intersections of technology, gender and labour. The Daily Digital framework offers valuable insights for (re)imagining gig work and advancing research and policy in the Global South.